Pemberdayaan Ekonomi Pengrajin Anyaman Tikar Pandan Aceh Timur melalui Inovasi Desain Kontemporer, dan Penguatan Manajemen Usaha, Pasca Banjir - Abdul Aziz; Jauharil Maknuni; Erni Wiriani; Selvi Mai Hetti; Ismail (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
The floods that struck East Aceh Regency have significantly affected the sustainability of pandan mat weaving enterprises, as reflected in declining production capacity, limited market access, and weak business management practices. This community service program aimed to strengthen the economic capacity of local artisans through contemporary design innovation and the enhancement of business management based on local wisdom. The program employed a Participatory Action Research (PAR) approach, involving a series of participatory stages, including needs assessment, training, mentoring, hands-on practice, and evaluation. The training covered product design development, basic financial record-keeping, cost of production calculation, and digital marketing strategies. The results demonstrated substantial improvements in participants' knowledge and skills in developing more innovative products, managing their businesses more systematically, and expanding market opportunities. Furthermore, the program fostered entrepreneurial awareness and enhanced the competitiveness of pandan weaving-based micro, small, and medium enterprises (MSMEs). Therefore, this initiative represents an effective and sustainable empowerment strategy for supporting the post-flood economic recovery of local communities.